Research of methods for identification of emergency modes of power supply system in transport infrastructure projects - Holub, Halyna; Kulbovskyi, Ivan; Skliarenko, Inna; Bambura, Olga; Tkachuk, Mykola (Technology audit and production reserves, 2019)
The object of research is the operating modes of the railway power supply system. Classification of emergency conditions based on the determination of damage for each of the feeders or phases is classic. The main causes of emergency conditions include various kinds of short circuits arising from damage to the insulation of phases, breaks and overvoltages. Damage to equipment occurs due to the natural aging of insulation, weathering and mechanical damage, switching overvoltages. A systematic approach, methods of system analysis, set theory, modern methods of image processing and intelligent data processing, ensuring the scalability of the developed methods are used. The methods for algorithmic solutions are investigated and mathematical models of processing and organizing the information space represented by sets of multidimensional data arrays with reference to the time domain, which is formed at the hierarchical levels of the corporate computer diagnostic system, are presented. The considered information space in its original form forms data that are considered as parametric images of processes received from microprocessor-based devices for recording system parameters. This is due to the fact that the methods for identifying emergency modes of electric power systems based on the corresponding parametric images of processes make it possible to obtain similar in structure algorithms for identifying modes for power systems of various types and purposes. This provides preliminary data processing for raising the parametric image of the emergency mode to the standard form of the matrix representation in the frequency domain. Compared with similar methods, this provides such advantages as the ability to run the diagnostic system both in “off-line” and in “on-line” modes. And the implementation of algorithmic solutions can be provided both at the lower level of diagnostic systems, and at the upper levels of power supply sections, as well as at the corporate level and can be characterized by the properties of scalability and flexibility with respect to the considered sections of power systems.